2007
DOI: 10.1007/s11274-007-9559-4
|View full text |Cite
|
Sign up to set email alerts
|

Degradative ability of 2,4,6-tribromophenol by saprophytic fungi Trametes versicolor and Agaricus augustus isolated from chilean forestry

Abstract: Trametes versicolor and Agaricus augustus, with a maximum tolerable concentration (MTC) of 80 lg ml -1 tribromophenol (TBP), were selected to evaluate TBP biodegradation capacity. These fungi were capable of decreased TBP concentrations and A. augustus was also capable of biotransforming TBP to tribromoanisole (TBA). Peroxidase and laccase activities were observed in the T. versicolor supernatant but not in that of A. augustus. These tolerance levels could be due to either lignolytic enzymes that degrade TBP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…PCP degradation test suggest that there is no relationship between tolerance and degradation ability. This result was previously reported by Donoso et al (2008), who studied the tolerance levels and degradation capacities of 2,4,6-tribromophenol by fungi isolated from Chilean forest and by Martinez et al (2000), who studied the tolerance and degradation of chlorophenols in bacteria. They indicated that these properties are not necessarily related.…”
Section: Pcp Degradation and Enzymes Productionsupporting
confidence: 83%
See 2 more Smart Citations
“…PCP degradation test suggest that there is no relationship between tolerance and degradation ability. This result was previously reported by Donoso et al (2008), who studied the tolerance levels and degradation capacities of 2,4,6-tribromophenol by fungi isolated from Chilean forest and by Martinez et al (2000), who studied the tolerance and degradation of chlorophenols in bacteria. They indicated that these properties are not necessarily related.…”
Section: Pcp Degradation and Enzymes Productionsupporting
confidence: 83%
“…However, the practical application of this fungus has been not always possible. Recent studies have focused on the search for other lignin-degrading strains capable to produce enzymes for various biotechnological applications (de Koker et al 2000;Machado et al 2005;Tekere et al 2001;Levin et al 2004;Guimarães et al 2006;Husain 2006;Donoso et al 2008). Husain (2006), reviewed the potential applications of several oxidoreductive enzymes (peroxidases, laccase, micro peroxidase) participating in the decolorization and degradation of dyes present in industrial effluents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some halogenated phenols can be biotransformed into corresponding methylated chemicals such as anisoles, veratroles, or guaiacols (Neilson et al, 1988;McNally and Harper, 1991). However, the xenobiotic methylation mechanism of TBP was still scarce (Donoso et al, 2008). Thus, a phenomenon of xenobiotic methylation deserved to identify during the biological debromination of TBP by the new-isolated strain Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…[11,[56][57][58][59][60][61][62][63][64][65]. This list may be expanded given the strong evidence for WRF degradation potential toward different classes of pollutants.…”
Section: Transformation Of the Herbicides By White-rot-fungimentioning
confidence: 99%